Control of river stage on the reactive chemistry of the hyporheic zone. Issue 17 (8th August 2013) - Byrne, P.; Binley, A.; Heathwaite, A. L.; Ullah, S.; Heppell, C. M.; Lansdown, K.; Zhang, H.; Trimmer, M.; Keenan, P.
Abstract We examined the influence of river stage on subsurface hydrology and pore water chemistry within the hyporheic zone of a groundwater‐fed river during the summer baseflow period of 2011. We found river stage and geomorphologic environment to control chemical patterns in the hyporheic zone. At a high river stage, the flux of upwelling water in the shallow sediments (>20 cm) decreased at sample sites in the upper section of our study reach and increased substantially at sites in the lower section. This differential response is attributed to the contrasting geomorphology of these subreaches that affects the rate of the rise and fall of a river stage relative to the subsurface head. At sites where streamward vertical flux decreased, concentration profiles of a conservative environmental tracer suggest surface water infiltration into the riverbed below depths recorded at a low river stage. An increase in vertical flux at sites in the lower subreach is attributed to the movement of lateral subsurface waters originating from the adjacent floodplain. This lateral‐moving water preserved or decreased the vertical extent of the hyporheic mixing zone observed at a low river stage. Downwelling surface water appeared to be responsible for elevated dissolved organic carbon (DOC) and manganese (Mn) concentrations in shallow sediments (0–20 cm); however, lateral subsurface flows were probably important for elevated concentrations of these solutes at deeper levels. Results suggest that DOC delivered to hyporheic sediments during a high river stage from surface water and lateral subsurface sources could enhance heterotrophic microbial activities. Copyright © 2013 John Wiley & Sons, Ltd.